The oral microbiome of children in health and disease—a literature review - AlHarbi, Salma G.; Almushayt, Abdullah S.; Bamashmous, Shatha; Abujamel, Turki S.; Bamashmous, Nada Othman (Frontiers in Oral Health, 2024)
The oral microbiome is a complex community of microorganisms residing in the oral cavity interacting with each other and with the host in a state of equilibrium. Disruptions in this balance can result in both oral and systemic conditions. Historically, studying the oral microbiome faced limitations due to culture-dependent techniques that could not capture the complexity and diversity of the microbial community. The emergence of advanced genomic technologies and the ease of sample collection from the oral cavity has revolutionized the understanding of the oral microbiome, providing valuable insights into the bacterial community in both health and disease. This review explores the oral microbiome in children, discussing its formation and dynamics in both states of health and disease, its role in various conditions such as dental caries, periodontal disease, oral cancer, cleft lip and palate, and explores its connection to several systemic consequences.